A formação do agente penitenciário no Estado do Pará - PAES, Bárbara de Nazaré da Silva (2020)
The present study of the course was proposed to know the professional training offered to prison agents in the state of Pará and the profile of these, based on bibliographical and documentary research, it was possible to produce contributions about the training of prison staff as well as glimpsing the challenges and difficulties faced by these professionals, and the importance of their work within the penitentiary system, through the performance of their duties and mainly as a mediator of the prisoner's social reintegration, was evidenced, although the profession since its inception did not receive due social recognition. The role of the penitentiary agent should be better seen and valued by society, better served by public and legislative policies, so that it can contribute, through positive actions in the prison environment, to the humanization of the prison. punishment, resocialization and king social integration of subjects in situations of deprivation of liberty.